To find the sum of matrices A and B, you can add the corresponding elements of the two matrices element by element. The resulting matrix will have the same dimensions as the original matrices.
For example, the element in the first row and first column of the sum of matrices A and B will be equal to the sum of the elements in the first row and first column of each matrix:
(A + B)11 = A11 + B11 = 1 + (-4) = -3
Similarly, the element in the first row and second column of the sum of matrices A and B will be equal to the sum of the elements in the first row and second column of each matrix:
(A + B)12 = A12 + B12 = (-1) + (-4) = -5
The element in the first row and third column of the sum of matrices A and B will be equal to the sum of the elements in the first row and third column of each matrix:
(A + B)13 = A13 + B13 = 1 + 0 = 1
Performing these calculations for all of the elements of the matrices, we find that the sum of matrices A and B is:
A + B = [-3 -5 1]
Therefore, the sum of matrices A and B is [-3 -5 1].